The eight : the Lemmon Slave Case and the fight for freedom - Rosenblatt, Albert M. (Albany, NY : Excelsior Editions, State University of New York Press, 2023)
"The personal and legal struggle of eight enslaved people for freedom in New York in the period just before the Civil War"--
Life in Bath County, Virgina -- From Virginia to New York -- Rescue -- At the courthouse -- We wish to plead our own cause -- Self-help for the slave owner -- Fugitives -- The court's ruling -- Life, liberty, or property -- The first appeal -- High stakes -- Privileges and immunities -- The voice of humanity -- The final ruling.
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Lemmon, Jonathan, -- active 1852-1860 -- Trials, litigation, etc; Slavery -- Law and legislation -- New York (State) -- History -- 19th century; Slavery -- United States -- Legal status of enslaved persons in free states; Habeas corpus -- New York (State) -- History -- 19th century -- Cases; Esclavage -- États-Unis -- Statut juridique des esclaves dans les États libres; 1800-1899; History; Trials, litigation, etc